Pengaruh motivasi, budaya kerja, komunikasi dan deskripsi pekerjaan terhadap kinerja ASN (Aparatur Sipil Negara) pada Dinas Perkebunan Dan Peternakan Sumatera Utara - Aristi Nurilla Faatin; Eka Umi Kalsum; M.Umar Mayaputra (BONANZA : Jurnal Ilmiah Ekonomi, Bisnis dan Keuangan, 2026)
The purpose of this study is to find out how the influence of motivation, work culture, communication and job descriptions on the performance of ASN (State Civil Apparatus) at the North Sumatra Plantation and Livestock Service.The method used was descriptive quantitative. Data collection techniques included questionnaires, interviews, observation, and literature review. The study population consisted of 143 respondents. The analysis technique used was multiple linear regression., These results indicate that motivation has a positive and significant effect, work culture has a positive and significant effect, communication has a positive and significant effect and job description has a positive and significant effect on the performance of ASN (State Civil Apparatus) at the North Sumatra Plantation and Animal Husbandry Service.